2018
DOI: 10.1080/00405000.2018.1535758
|View full text |Cite
|
Sign up to set email alerts
|

Air permeability and bursting strength of weft-knitted fabrics from glass yarn. Part II: knit architecture effect

Abstract: In this study; the effects of loop, skip, and tuck stitch types, and weft-inlay yarn, on air permeability and bursting strength of weft-knitted fabrics from glass yarn were revealed. Due to clockwise rotation of wales and their arrangement being one on top of the other, besides the dramatic shortening of fabrics after their removal from the machine; fabrics with tuck stitches exhibited the highest stitch density, fiber content, and the shortest loop length. This caused the lowest air permeability and the highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
0
3
0
2
Order By: Relevance
“…Similarly, the number and position of the tuck stitches in single-bed cotton yarn weft knit fabrics significantly affected the properties of the fabric and the tuck stitch increased the fabric thickness and areal density in the previous studies [23][24][25]. İnce and Yıldırım [26] also observed that the tuck stitch increased the thickness and areal density in single-bed glass yarn weft knit fabrics because of left to right turning and nesting of the loop bars.…”
Section: Thickness Areal Density and Fiber Volume Percentmentioning
confidence: 75%
“…Similarly, the number and position of the tuck stitches in single-bed cotton yarn weft knit fabrics significantly affected the properties of the fabric and the tuck stitch increased the fabric thickness and areal density in the previous studies [23][24][25]. İnce and Yıldırım [26] also observed that the tuck stitch increased the thickness and areal density in single-bed glass yarn weft knit fabrics because of left to right turning and nesting of the loop bars.…”
Section: Thickness Areal Density and Fiber Volume Percentmentioning
confidence: 75%
“…Önceki çalışmalarda tek iğne yatağı kullanılarak pamuk ipliğinden üretilen atkılı örme kumaşlarda da askı ilmeğinin sayısı ve pozisyonu kumaşın fiziksel özelliklerini ve kullanım performansını önemli ölçüde etkileyerek kalınlık ve alansal yoğunluğu arttırmıştır [1,9,10]. Benzer şekilde İnce ve Yıldırım [11] cam ipliğinden tek iğne yatağı kullanarak ürettikleri atkılı örme kumaşlarda askı ilmeğinin kumaş kalınlığını ve alansal yoğunluğunu arttırdığını gözlemlemiş ve bu artışı ilmek çubuklarının saat ibreleri yönünde dönerek yuvalanmalarına bağlamıştır. 2x2 ribana örgü deseninde düz ve ters ilmek çubuklarının ikili ve ardışık yerleşimi kumaş iç gerilimini arttırmış ve bu iç gerilim de makineden çıkarılan kumaşın ilmek sırası (kumaş eni) yönünde dramatik bir şekilde daralmasına neden olmuştur.…”
Section: Kalınlık Alansal Yoğunluk Ve Lif Hacmi Yüzdesiunclassified
“…İnce ve Yildirim [11] tek iğne yatağı kullanarak cam ipliğinden ürettikleri atkılı düz örme kumaşlarda farklı ilmek tiplerinin hava geçirgenliği ve patlatma mukavemeti üzerine etkisini incelemiştir. Makineden alınan askı ilmekli kumaşın dramatik bir şekilde kısalarak ilmek çubuklarının saat ibreleri yönünde dönmesi ve birbiri üzerlerine yerleşmeleri ilmek yoğunluğunu ve lif içeriğini arttırırken ilmek uzunluğunu azaltmıştır.…”
Section: Introductionunclassified
“…The air permeability of textiles has been widely analyzed by many researchers and it is well known that it depends on such factors as structural parameters of the fabric, porosity, thickness, density, finishing, linear density of yarns, and composition of the yarn. 1721…”
mentioning
confidence: 99%
“…The air permeability of textiles has been widely analyzed by many researchers and it is well known that it depends on such factors as structural parameters of the fabric, porosity, thickness, density, finishing, linear density of yarns, and composition of the yarn. [17][18][19][20][21] Previous research has shown that the thermal properties of textile fabrics depend on the fabric's thickness and porosity, therefore, fabrics knitted in combined patterns have higher thermal resistance than plain plaited fabrics because of the higher thickness of the combined structures. 22 As the thickness of fabrics knitted from the same raw material increases, thermal resistance also increases, which means that thicker knitted fabrics are warmer.…”
mentioning
confidence: 99%